Acquisition and utilisation of anthropometric measurements on admission in a paediatric hospital before and after the introduction of a malnutrition screening tool. Issue 3 (8th April 2013) - Milani, S.; Wright, C.; Purcell, O.; Macleod, I.; Gerasimidis, K.
Abstract Background Acquisition of anthropometric measurements and assessment of growth in paediatric inpatients remains poor. The introduction of malnutrition screening tools that incorporate weight and height/length measurements might improve their acquisition and utilisation in other aspects of patient care. Methods Documentation of weight and/length measurements and their plotting on growth charts was evaluated using a case notes review in paediatric inpatients who were admitted before (n = 146), during (n = 154) and after the pilot (n = 151) and official (n = 128) clinical use of a screening tool. Results Documentation of weight was high in all periods (> 97% of patients). Height/length measurement documentation was negligible (4% of patients) but improved after the introduction of the screening tool (> 62%; P < 0.0001), except in infants, who were not part of the screening programme. Conclusions Introduction of a screening tool improved the acquisition of anthropometric measurements by nursing staff, although its utilisation by medical staff remained poor.